A survey of political interference patterns and modalities in national roadworks in the Philippines - Batalla, Eric Vincent C. (Animo Repository, 2018)
This study surveys and describes the patterns or modalities of political interference in national roadworks in the Philippines based on an examination of the literature and interviews using process-level frameworks, specifically the project management cycle and the budget cycle framework. Political interference here refers to non-legitimate interventions by politicians in government processes and programs. We argue that it is a form of political corruption. Evidence suggests that this type of interference tends to be prominent in national roadworks. Executive interference occurs at various stages of the project management and budget processes. The abuse of executive discretion in national road development is observed from project selection and prioritization to project maintenance and evaluation. Legislator interference appears to occur at various stages of the project management cycle based on collusive and kickback arrangements. In the budget cycle, this is most notable during the budget legislation stage. Given these vulnerabilities, a comprehensive review of existing project and budget management systems is necessary with the view of reducing such abuse. Finally, understanding the historical and institutional (socio, economic, political, and cultural) context under which these systems operate is necessary to identify context-specific solutions. © 2018 by De La Salle University.